Determination of the insecticidal effects of four different insecticides against Acanthoscelides obtectus (Say) (Coleoptera: Bruchidae) - Buran, Abayhan; Ozgen, Inanc; Gural, Yunus; Yilmaz, Kadir Gorkem (Springer, 2025)
Background This study utilised the compounds Grainpro AITC-Alpha, Grainpro AITC-Gamma, Grainpro Gamma-Eug, and Grainpro AITC-Euc. Previous studies have not investigated the statistical details of the lethal effects of these compounds on Acanthoscelides obtectus.The objective of the experiments was to demonstrate the high lethal effect of all compounds on A. obtectus and to ascertain how the insecticidal effect changed with increasing concentration. Results Grainpro AITC-Alpha, one of the most effective compounds, reached 100% mortality by the 3rd day and showed efficacy even at low concentrations. Similarly, the other compounds demonstrated rapid and effective lethality at high concentrations. Statistical analyses indicated that all compounds had significantly higher mortality rates compared to the control group (p < 0.05). LD50 and LD90 values showed that Grainpro AITC-Alpha was the most effective compound at the lowest concentration. According to LT50 and LT90 values, Grainpro AITC-Gamma was the most effective compound at the lowest concentration. Conclusions In conclusion, plant-based insecticides can be used as an alternative to chemical pesticides against A. obtectus, and their integration into biological control strategies during storage processes is recommended.This study highlights the potential of plant extracts as an environmentally friendly and effective pest control method.
Keywords: Acanthoscelides obtectus; Plant extracts; Insecticidal effect; LD50; LT50; LD90; LT90